Grafiek in West-Vlaanderen 1971 : kataloog. - Gildhof, Tielt; Provinciaal Hof, Brugge (Brugge : Provincie West-Vlaanderen, 1971)
Hoorne, Emiel ; Ghislain, Kuyle ; Gheysens, Moniek ; Huybrechs, Marie-Christine ; Schotte, Monique ; Vandekerkhove, Rita ; Meuleman, Michel ; De Blaere, Horst ; De Buysere, Leo ; Demarest, Jan ; De Sauter, Willy ; Dewaele, Daniël ; Lagrou, Luc ; Lysens, Mariette ; Rubens, Albert ; Seys, Walter ; Soubry, Bart ; Vanallemeersch, Geert ; Vanhoutte, Annie ; Verbeke, Jan ; Verduyn, Jacques
Grafiek in West-Vlaanderen 1971, Gildhof, Tielt, 23/10 - 11/11/1971 ; Provinciaal Hof, Brugge, 21/11 - 12/12/1971
kunstcatalogus